(untitled) (Research, Society and Development, 2020)
The construction industry is responsible for the generation of large volumes of waste, known as construction and demolition waste (CDW). Around the world, millions of tons of these wastes are generated annually, which often become important environmental liabilities. The situation gets worse as the sector develops. In Europe, only 15 of the 27 countries in the European Union annually produce around 180 million tonnes of CDW, in Brazil, the data about this indicates that in 2014 the municipalities collected about 45 million tons of CDW, quantity 4.1% higher than in 2013. In this scenario, the present study aims to evaluate the partial replacement of natural aggregates by CDW (aggregates of concrete waste) in the production of concretes. In this sense, the effects of this substitution on the workability and mechanical characteristics of the concretes produced, as well as the influence of the mixing method and the percentage of superplasticizer additive on the same characteristics were evaluated. The methodology basically consists in the production of seven different traits, which are references and different combinations of mixing method, aggregate substitutions and superplasticizer percentages. Specimens of these traces were molded for mechanical characterization. Workability parameters were also evaluated. It is concluded that the workability is strongly affected by the addition of CDW, but a good workability can be obtained with the use of superplasticizer additives. The mixing method did not change the results obtained for this property. The results also indicate that the compressive and tensile strengths are not negatively affected by the substitution of aggregates, as well as being not significantly affected by the presence of the percentages of superplasticizer used, nor by the mixing methods.